2004
DOI: 10.1016/s1090-3801(03)00086-7
|View full text |Cite
|
Sign up to set email alerts
|

Key role of the dorsal root ganglion in neuropathic tactile hypersensibility

Abstract: Cutting spinal nerves just distal to the dorsal root ganglion (DRG) triggers, with rapid onset, massive spontaneous ectopic discharge in axotomized afferent A-neurons, and at the same time induces tactile allodynia in the partially denervated hindlimb. We show that secondary transection of the dorsal root (rhizotomy) of the axotomized DRG, or suppression of the ectopia with topically applied local anesthetics, eliminates or attenuates the allodynia. Dorsal rhizotomy alone does not trigger allodynia. These obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(87 citation statements)
references
References 62 publications
(87 reference statements)
4
77
0
3
Order By: Relevance
“…The present study demonstrated that in the injured L5 DRG, most of the p-ERK-IR neurons and a subpopulation of p-p38-IR neurons were large in size and that the ERK and p38 inhibitors reversed the L5 SNL-induced mechanical allodynia. Furthermore, L5 dorsal rhizotomy prevented the development of mechanical allodynia, as reported previously (Yoon et al, 1996;Sukhotinsky et al, 2004). These observations support the possibility that large-diameter A-fibers mediate mechanical allodynia, whereas nociceptive C-fibers mediate thermal hyperalgesia Pan et al, 2003).…”
Section: Mapk Activation In the Injured L5 Drg Neurons And Mechanicalsupporting
confidence: 88%
“…The present study demonstrated that in the injured L5 DRG, most of the p-ERK-IR neurons and a subpopulation of p-p38-IR neurons were large in size and that the ERK and p38 inhibitors reversed the L5 SNL-induced mechanical allodynia. Furthermore, L5 dorsal rhizotomy prevented the development of mechanical allodynia, as reported previously (Yoon et al, 1996;Sukhotinsky et al, 2004). These observations support the possibility that large-diameter A-fibers mediate mechanical allodynia, whereas nociceptive C-fibers mediate thermal hyperalgesia Pan et al, 2003).…”
Section: Mapk Activation In the Injured L5 Drg Neurons And Mechanicalsupporting
confidence: 88%
“…The ectopic firing then leads to initiation and maintenance of central sensitization (Sukhotinsky et al 2004;Devor 2006), most likely due to neurochemical changes taking place in the spinal cord (e.g., Ji and Woolf 2001). In line with this interpretation, when the ectopic peripheral input was suppressed, central sensitization decreased and MA was eliminated (Devor 2006).…”
Section: Introductionmentioning
confidence: 78%
“…As outlined in the Introduction, mechanical allodynia emphasizes its central sensitization, in particular in the dorsal root ganglion or in the dorsal horn (e.g., Woolf 1983;Hendry et al 1999;Mannion et al 1999;Sindrup et al 1999;Ji and Woolf 2001;Ji et al 2003;Sukhotinsky et al 2004;Devor 2006). The statement ''The static mechanical allodynia is a paradoxical painful hypoaesthesia'' does not contest the most likely central component of post-injury pain hypersensitivity (Woolf 1983).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations